Exposure to Biracial Faces Reduces Colorblindness. (January 2019) - Gaither, Sarah E.; Toosi, Negin R.; Babbitt, Laura G.; Sommers, Samuel R.
Across six studies, we demonstrate that exposure to biracial individuals significantly reduces endorsement of colorblindness as a racial ideology among White individuals. Real-world exposure to biracial individuals predicts lower levels of colorblindness compared with White and Black exposure (Study 1). Brief manipulated exposure to images of biracial faces reduces colorblindness compared with exposure to White faces, Black faces, a set of diverse monoracial faces, or abstract images (Studies 2-5). In addition, these effects occur only when a biracial label is paired with the face rather than resulting from the novelty of the mixed-race faces themselves (Study 4). Finally, we show that the shift in White participants' colorblindness attitudes is driven by social tuning, based on participants' expectations that biracial individuals are lower in colorblindness than monoracial individuals (Studies 5-6). These studies suggest that the multiracial population's increasing size and visibility has the potential to positively shift racial attitudes.